6x-3x-4=0

Simple and best practice solution for 6x-3x-4=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-3x-4=0 equation:



6x-3x-4=0
We add all the numbers together, and all the variables
3x-4=0
We move all terms containing x to the left, all other terms to the right
3x=4
x=4/3
x=1+1/3

See similar equations:

| -10-7x=-(5x+4) | | 7n-8=2(2n+5) | | x/5+1=-5 | | 2n-25=93 | | x/3-2=-6;x= | | -6n-3(3-3n)=33+8n | | 6p-13=5(4-p) | | m-2=5(7m-7)-1 | | 3y(y-3)=(3y-4)(y+5) | | 6k-7=7k-11 | | 6x-x+10=15 | | -11x-16=60 | | x/8-5=-11 | | 31+2m=-8+7(-6m-7) | | 2/3+3/y=5y-2/15 | | 27.50x+1,200=20x+1,400 | | x/6+3=0;x= | | 6-7v=-8 | | 2/3+3/y=5y/1-2/15 | | 45.99+18.00x+6.75x=144.99 | | 8,2x+3,7=2,5x+28,9 | | 3+2x=2(2+x | | 58-3x=4×-5 | | -2/5x=-2/9 | | 4x-3=6x+22 | | 40.00+15.25x+9.50x=213.25 | | x/6+3=0 | | 240x+1/4=180x+2/5 | | 6x+36=2x-2 | | 42r=243 | | x/11+4=1 | | 6+8p=1+9p |

Equations solver categories